Estado de la salud mental ante la covid-19 en el personal administrativo del Municipio de Loja. - Erique Avila, Claudia Maribel (2022)
The COVID-19 pandemic has not only caused consequences in the physical health of infected people and a high number of deaths worldwide, but the control measures that have been implemented have had a negative impact on the psychological well-being and mental health of the population. The following research aims to describe the characteristics related to mental health in the administrative personnel of the Municipality of Loja during the COVID-19 pandemic, as well as, it performs a characterization of the sociodemographic and labor factors of the participants of the study, seeking to identify their family and behavioral conditions, while identifying the symptoms related to depression, anxiety, stress. Moreover, a non-experimental, descriptive, quantitative, prospective cross-sectional cohort design study was carried out, by applying the Depression, Anxiety and Stress Scale (DASS-21). As a result, a total of 132 administrative staff participated, in which 72.7% were men. Additionally, about 88.64% of the participants reported not having had mental health problems in the past, while 78.64% claimed not having these problems during the pandemic. However, psychological distress reached figures with significant effect, 26.4% of the respondents presented depressive symptomatology, 31.68% anxiety and 22.44% stress; women and young adults were the groups most affected by the symptoms evaluated. These results advocate intervention actions aimed at the prevention, diagnosis and treatment of these alterations, in order to reduce the impact on mental health caused by the COVID-19 pandemic.